1992
DOI: 10.1002/j.1537-2197.1992.tb14594.x
|View full text |Cite
|
Sign up to set email alerts
|

Monomorphism, Reduced Gene Flow, and Cleistogamy in Rare and Common Species of Lespedeza (Fabaceae)

Abstract: Population genetic structure was analyzed in the rare, native prairie legume Lespedeza leptostachya Engelm. and in the widespread L. capitata Michx. Both species produce a mixture of chasmogamous and cleistogamous flowers. Allozymes were analyzed for 32 loci from 224 individuals from 12 populations of L. leptostachya and for 34 loci in 291 individuals from 12 populations of L. capitata. L. leptostachya is entirely monomorphic at all loci studied, while L. capitata shows strong among‐population differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…Additionally, the findings of higher genetic diversity among invasive L. cuneata populations in relation to native Lespedeza populations (Cole and Biesboer 1992;Sundberg et al 2002) are consistent with our finding that the invasive L. cuneata maintains an insect visitation rate eight to ten times that of the native Lespedeza species. This higher insect visitation rate suggests a higher degree of gene flow through pollination than its native congeners.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the findings of higher genetic diversity among invasive L. cuneata populations in relation to native Lespedeza populations (Cole and Biesboer 1992;Sundberg et al 2002) are consistent with our finding that the invasive L. cuneata maintains an insect visitation rate eight to ten times that of the native Lespedeza species. This higher insect visitation rate suggests a higher degree of gene flow through pollination than its native congeners.…”
Section: Discussionsupporting
confidence: 90%
“…Although all extant populations of L. helleri can be found within a 30 km radius in North Carolina, the species maintains relatively high levels of genetic variation. Comparative studies of congeneric species with differing ranges have frequently revealed lower levels of variation in the more narrowly distributed species, although this result has not been entirely consistent (Karron, 1987;Karron et al, 1988;Cole and Biesboer, 1992). Thus, the genetic diversity in this threatened species is about three times the mean genetic diversity found for endemic plants.…”
Section: Discussionmentioning
confidence: 89%
“…However, this range is not unique among CH/CL species (e.g. Cole & Biesboer, 1992). The value of θ derived from the allozyme data (0.29) was significantly different from zero (Table 3), indicating that genetic differentiation occurred among the sampled populations.…”
Section: Resultsmentioning
confidence: 99%